2012
DOI: 10.1590/s1808-16572012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Biologia e tabela de vida de fertilidade de Spodoptera frugiperda (J.E. Smith) em linhagens de milho

Abstract: RESUMOO objetivo deste trabalho foi estudar os aspectos biológicos de Spodoptera frugiperda (J. E. Smith) e elaborar a tabela de vida de fertilidade deste inseto em cinco linhagens de milho provenientes do Programa de Melhoramento de Milho da Embrapa Clima Temperado. Foram determinadas a duração e sobrevivência das fases de ovo, larva, pré-pupa e pupa, peso de pupas, deformações, longevidade, fecundidade e período de pré-oviposição. A linhagem M89611 não permitiu aos insetos realizarem postura. A duração do pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
2
3
0
1
Order By: Relevance
“…The average generation time (T) found in this study was similar to those obtained by Rosa et al (2012) with S. frugiperda on five maize lines (between 21.3 and 45.7 d). The values of the net reproduction rate (R 0 ), the intrinsic increase rate (r m ) and the finite increase rate (λ) differed from those obtained by Omoto et al (2016) in non-Bt maize, who measured 272.0, 0.152, and 1.165, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The average generation time (T) found in this study was similar to those obtained by Rosa et al (2012) with S. frugiperda on five maize lines (between 21.3 and 45.7 d). The values of the net reproduction rate (R 0 ), the intrinsic increase rate (r m ) and the finite increase rate (λ) differed from those obtained by Omoto et al (2016) in non-Bt maize, who measured 272.0, 0.152, and 1.165, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The incubation period of S. frugiperda eggs fed on sorghum cultivars BRS 506 and BRS 511 during the larval phase lasted three days, with no significant differences (Table 1). Results corroborated those by Rosa et al (2012) who reported rates between 2.8 and 3.3 days when they studied the biological aspects of S. frugiperda fed on corn strains. There was no time duration for insects fed on cultivar BRS 509 since the adults failed to lay any eggs.…”
Section: Resultssupporting
confidence: 90%
“…Velez and Sifuentes (1967) performed a study with corn leaves, the preferred food of the insect and concluded that the incubation period of S. frugiperda was 4 days. In other studies, feeding two populations of S. frugiperda with Pioneer 30F33 corn, the authors observed an incubation period of 2.4 and 2.7 days, which reached 3.3 and 3.2 days with the strains M89601 and M89420, respectively (BUSATO et al, 2005;ROSA et al, 2012).…”
Section: Resultsmentioning
confidence: 79%
“…In this study, adult longevity was 6.7 (azevém) and 5 days (cornichão) ( Table 2). In studies with corn strains, Rosa et al (2012) found that the duration of the adult phase was 14 days for the M89601 lineage and 21 days for the M89287 lineage. This may be related to tannin present in the food ingested during the larval stage, leading to increased longevity of adults (LUGINBILL, 1928).…”
Section: Resultsmentioning
confidence: 99%